Kween - Chum, Vichet (Quill Tree Books, an imprint of HarperCollinsPublishers, 2023)
"With her first video posted to social media, Soma Kear has become a viral MC. Trouble is, she didn't exactly think the whole thing through. All Soma knew was that her rhymes were urgent. They were on fire. They were an expression of where she was, and that place...was a hot mess. Soma's ba was deported back to Cambodia six months ago, and it's changed everything. Her ma's been away, trying to help her father acclimate to his new life, and against Soma's wishes her older sister, Dahvy, has moved back in with a brand-new authoritarian tone. Meanwhile, Soma's video has moved from small-town hype to actually trending, pushing the budding MC to ask herself if it's time to level up. With her school's spoken word contest looming, Soma must decide: Is she brave enough to put herself out there? To publicly reveal her fears of Ba not returning? To admit to herself that things may never be the same? With every line she spits, Soma is searching for a way to make sense of the world around her. The answers are at the mic." --